2018
DOI: 10.1186/s12199-018-0709-0
|View full text |Cite
|
Sign up to set email alerts
|

Expert clinician’s perspectives on environmental medicine and toxicant assessment in clinical practice

Abstract: BackgroundMost clinicians feel ill-equipped to assess or educate patients about toxicant exposures, and it is unclear how expert environmental medicine clinicians assess these exposures or treat exposure-related conditions. We aimed to explore expert clinicians’ perspectives on their practice of environmental medicine to determine the populations and toxicants that receive the most attention, identify how they deal with toxicant exposures and identify the challenges they face and where they obtain their knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In light of this model, distracting attention from odorous or pungent substances may be effective for the recovery from CI status, resulting in the treatment of CI. In the clinical practice, adequate assessment of exposure history for identifying the agent substance which should be avoided would have an important role for the recovery of a patient with CI [100]. Interestingly, a 5-year follow-up study reported that appropriate physical activity and maintaining a regular lifestyle, including diet or sleep, were significant factors for the improvement of CI [101].…”
Section: Methodsmentioning
confidence: 99%
“…In light of this model, distracting attention from odorous or pungent substances may be effective for the recovery from CI status, resulting in the treatment of CI. In the clinical practice, adequate assessment of exposure history for identifying the agent substance which should be avoided would have an important role for the recovery of a patient with CI [100]. Interestingly, a 5-year follow-up study reported that appropriate physical activity and maintaining a regular lifestyle, including diet or sleep, were significant factors for the improvement of CI [101].…”
Section: Methodsmentioning
confidence: 99%
“…While the saliva exposome studies published elsewhere [ 85 ] were able to capture the endogenous and therapeutic agent-derived compounds/metabolites, pollutants were not represented in detail in that report due to lack of sufficient data. Both the clinician and basic scientist continue to face challenges in assessing toxicant loads in the absence of comprehensive educational resources, definitive laboratory tests, established dose–response relationships or exposure history tools [ 86 ]. A timeline of exposure history will continue to be the most useful clinical tool for assessing toxicant exposures, until standardized assessment tools can be calibrated to be applied universally.…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…However, adapting their knowledge to the needs of patients is not always clear due to the lack of literature on EM clinical practice and little qualitative research on the perspectives of environmental professionals. EM practitioners can be divided into two main groups: integrative physicians (IP) who use knowledge from other medical disciplines to treat patients with chronic, complicated, misdiagnosed conditions involving multiple systems and environment physicians (OEP) who treat employees based on their occupational exposure to toxic substances [29]. However, while in developed countries, these two types of practices exist separately, in Albania neither of them exists.…”
Section: Importance and Development Of Specific Undergraduate Or Postgraduate Programs In The Field Of Environmental Medicine In The Casementioning
confidence: 99%